Functioning and quality of soils cultivated with sugarcane under different tillage and soil management systems - Martíni, Aline Fachin (2024)
The production sustainability of sugarcane cultivation has been a growing concern, especially because the cultivation system used by the majority of producers has led to soil quality degradation and compromised agricultural production. Therefore, in order to meet the global demand for biofuels, it is essential that the cultivation systems employed do not compromise soil quality and economic as well as environmental sustainability. To gather information about the current scenario, an investigation was conducted into how soil quality has been addressed in research on sugarcane management, aiming to identify gaps that need further exploration in future studies. A bibliometric review revealed gaps in studies involving sugarcane cultivated under conservationist systems, such as no-tillage, that comprehensively assess soil quality through the integration of physical, chemical, and biological indicators. Additionally, there is a need for analyses of hydrophysical, micromorphological, and macrofauna aspects as indicators of soil quality. Building upon these findings, the objective was to evaluate the functioning and quality of soil cultivated with sugarcane under different soil preparation and management systems, including conservationist systems, to identify the system that most contributes to improving the sustainability of sugarcane production. For this purpose, a long-term trial (conducted since 1998) was utilized, where sugarcane and soybeans are cultivated in a rotational system under conventional tillage and no-tillage systems with varying lime doses. Through physical and hydrophysical analyses, as well as visual assessments of soil structure, the functioning and quality of the soil were evaluated. Overall, the results indicated that the no-tillage system in conjunction with lime application (4 Mg ha-1) emerges as the most viable system for soil conservation and the environmental and economic sustainability of sugarcane cultivation. This system combines the advantages of correcting soil fertility through liming with the benefits of no-tillage, enhancing hydrophysical attributes and soil structure.